2011
DOI: 10.1371/journal.pone.0024063
|View full text |Cite
|
Sign up to set email alerts
|

Lys98 Substitution in Human AP Endonuclease 1 Affects the Kinetic Mechanism of Enzyme Action in Base Excision and Nucleotide Incision Repair Pathways

Abstract: Human apurinic/apyrimidinic endonuclease 1 (APE1) is a key enzyme in the base excision repair (BER) and nucleotide incision repair (NIR) pathways. We recently analyzed the conformational dynamics and kinetic mechanism of wild-type (wt) protein, in a stopped-flow fluorescence study. In this study, we investigated the mutant enzyme APE1K98A using the same approach. Lys98 was known to hydrogen bond to the carboxyl group of Asp70, a residue implicated in binding the divalent metal ion. Our data suggested that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 34 publications
1
18
0
Order By: Relevance
“…In the last decade, Nucleotide Incision Repair (NIR) pathway has been described as a new function of APE1 which works as back up of BER pathway ensuring a correct removal of damaged bases as a result of oxidative stress [20][21][22][23][24][25]. NIR activity by APE1 consists of an incision at the 5′ next to a oxidatively damaged base in a DNA glycosylase-independent manner, providing a proper 3′-OH group for further processing [20].…”
Section: Nir Activity Of Ape1 On Non-canonical Substratesmentioning
confidence: 99%
See 2 more Smart Citations
“…In the last decade, Nucleotide Incision Repair (NIR) pathway has been described as a new function of APE1 which works as back up of BER pathway ensuring a correct removal of damaged bases as a result of oxidative stress [20][21][22][23][24][25]. NIR activity by APE1 consists of an incision at the 5′ next to a oxidatively damaged base in a DNA glycosylase-independent manner, providing a proper 3′-OH group for further processing [20].…”
Section: Nir Activity Of Ape1 On Non-canonical Substratesmentioning
confidence: 99%
“…Interestingly, the N-terminal domain of APE1 deputed to modulate proteinprotein interaction and indispensable to redox activity but not APendonuclease activity [38], is contrarily essential for the NIR activity; indeed the lack of the first 33 N-terminal aminoacids of the protein produces a 20-fold-decrease of APE1 NIR activity [20]. Moreover, Timofeyeva et al demonstrated that Lysine in position 98 contributes significantly in the 5′-phospodiester bond hydrolysis of DNA substrate, but not in the dissociation of the enzyme-product complex [21]. Interestingly, the substitution of this amino acid influences the APE1 NIR activity more than BER, demonstrating that the APE1 active site involved in NIR and BER pathways is the same, but different conformational requirements are responsible for APE1 NIR or BER activities [21].…”
Section: Nir Activity Of Ape1 On Non-canonical Substratesmentioning
confidence: 99%
See 1 more Smart Citation
“…The enzyme-substrate complex undergoes induced fit upon binding to lesion. Substitution K98A in APE1 has an "effect on induced fit" preventing it and decreasing the stability of enzyme-substrate complex (Timofeyeva et al 2011). …”
Section: Effect On Protein Dynamicsmentioning
confidence: 99%
“…This lesion would have been generated by the 5' incision repair activity of APEX1 (Timofeyeva et al 2011). Methylation of both C residues on both strands in the CpG islet, e.g.…”
Section: Creb1's Ability To Bind To Its Consensus Sequence Is Affectementioning
confidence: 99%